DAMPAK PARTISIPASI DALAM PERENCANAAN STRATEGIS TERHADAP BUDGETARY SLACK: AUTONOMUS BUDGET MOTIVATION DAN KEADILAN PERSEPSIAN - Qurba, Glen Lazwardi; Soenaria, Syaiful Rahman; A, Gia Kardina Prima (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
Budgetary slack are influenced by factors such as information asymmetry, the complexity of tasks, organizational commitments, and environmental uncertainty. However, there were inconsistencies in the results of previous studies. The study aims to test the influence of participation in strategic planning through fair perception and autonomous budget motivation against budgetary slack. The methods used in this research are descriptive and verification methods with a quantitative approach. The analytical unit in this study is an individual with a Manager position involved in the process of drafting a budget proposal for the 20XX shipping company. The research data is taken using the survey method, with the total population of the study is 90 people, the sampling method used is purposive sampling. As for data analysis techniques using Partial Least Square – Structural Equation Modelling (PLS – SEM). Based on the results of the research, it can be concluded that the participation of managers in strategic planning significantly positively affects the fairness of perception and autonomous budget motivation perceived by middle-level managers and can reduce the budget gaps that occur in the organization.